Development of IFN-gamma resistance is associated with attenuation of SOCS genes induction and constitutive expression of SOCS 3 in melanoma cells - Fojtová, Miloslava; Boudný, Vladimír; Kovařík, Aleš; Lauerová, Ludmila; Adámková, Lenka; Součková, Kamila; Jarkovský, Jiří; Kovařík, Jan (British journal of cancer, 2007)
The resistance to interferons (IFNs) limits their anticancer therapeutic efficacy. Here we studied the evolution of an IFN-resistant state in vitro using melanoma cell lines. We found that the cells became less sensitive to antiproliferative effect of IFN-gamma after prolonged cultivation enabling us to isolate sensitive and resistant subclones of the parental line. We investigated transcription of signal transducer and activator of transcription (STAT) 1-6 and suppressor of cytokine signalling (SOCS) 1-3 genes, and phosphorylation of STAT 1 protein. The resistant subline (termed WM 1158R) differed from the sensitive subline (WM 1158S) by a constitutive expression of SOCS 3, lack or weak SOCS 1-3 activation following IFN-gamma, and short duration of cytokine activatory signal. Similar correlations were observed in additional melanoma lines differing in IFN sensitivities. At the protein level, IFN-gamma induced strong and prolonged STAT 1 activation at serine 727 (S727) in WM 1158R while in WM 1158S cells phosphorylation of this amino acid was much less pronounced. On the other hand, phosphorylation of tyrosine 701 (Y701) was stimulated regardless of the sensitivity phenotype. In conclusion, constitutive expression of SOCS 3 is correlated with attenuation of its induction following IFN treatment. These results suggest that progression of melanoma cells from IFN sensitivity to IFN insensitivity associates with changes in SOCS expression.
Keywords: Gene Expression Regulation, Neoplastic; financování organizované; STAT1 Transcription Factor; transkripční faktor STAT1; interferon gama; Financing, Organized; proliferace buněk; Cell Line, Tumor; Humans; Interferon-gamma; Gene Expression; lidé; stanovení celkové genové exprese; Skin Neoplasms; exprese genu; Cell Proliferation; chemorezistence; fosforylace; Melanoma; Suppressor of Cytokine Signaling Proteins; Phosphorylation; proteiny SOCS; nádorové buněčné linie; melanom; Gene Expression Profiling; nádory kůže; regulace genové exprese u nádorů; Drug Resistance, Neoplasm